Pengembangan ASEAN Qualification Recognition Framework (AQRF) tentang Standardisasi Manajemen Halal sebagai Strategi Sukses ASEAN Free Trade Area (AFTA) - Hamzah Robbani; Mualimin Mochammad Sahid (LITERATUS, 2021)
This study aims to harmonization of halal in countries in ASEAN. This is done by stating several things, including: Analyzing halal practice standards in ASEAN countries, Aligning halal standards between ASEAN and developing AQRF on halal management. This study uses a qualitative method. The philosophical world view in this study is more attached to a pragmatic world view, this world view is based on applications and solutions to existing problems (Patton in Cresswell, 1990). From the point of view of research design, the researcher uses a case study design, the researcher develops an in-depth analysis of a case, program, event, activity, or process in one or more individuals. In the case study design approach, the researcher limits time and activities. Information collection is carried out by various data collection procedures. Data collection techniques used in this study are; 1. Interviews, 2. Content-relevant analysis of documents, 3. Round table. Based on the results that have been obtained that Indonesia has the ability to carry out production procedures that are guaranteed halal from each process. However, a thorough halal audit needs to be carried out consistently. This is supported by research conducted by Hudaefi & Jaswir (2019) that Indonesia with the largest Muslim population in Indonesia has become a leader in the world halal industry (Detik Finance, 2011; Republika, 2010; Safari, 2018; Satria, 2012).